Kisah Cinta Platonik Jalâl al-Dîn al-Rûmî - Zayyin Alfi Jihad (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2011)
The research attempts to discover and find the very roots of the love concept by Jalâl al-Dîn Rûmî to develop the Sufism method, which connects human’s hearts with their God. This study employs a philosophical qualitative method, which tends to be descriptive and interpretative. Using the basis of love, Jalâl al-Dîn Rûmî built a Sufistic epistemological foundation in the form of mystical poems. Poems are a means of spiritual pilgrimage, which is performed to find the culmination of fusion ecstasy between humans and their God, i.e., Allah The Almighty.